Teaching tropical design through simulating scale models - Chua, Johannes Vincent F. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2020)
Access online through this link: https://journals.upd.edu.ph/index.php/muhon/article/view/7338/6424